A systematic review and meta-analysis of the risk for development of varicose veins in women with a history of pregnancy - Ismail, Lars; Normahani, Pasha; Standfield, Nigel J.; Jaffer, Usman (Journal of vascular surgery. Venous and lymphatic disorders, 2016)
Objective - The association between pregnancy and the development of varicose veins is uncertain. We aimed to determine whether a history of pregnancy is associated with the development of varicose veins. - Methods - We performed a systematic literature search using the databases of PubMed, Embase, Robert Koch-Institut, and Cochrane Central and the references of included papers. Eligible studies were all epidemiologic observational studies in which the outcome “varicose veins” and pregnancy history were assessed. The quality of each study was evaluated on the basis of the Dutch Cochrane review checklist and by the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement. For our meta-analysis, a random effects model was applied to pool odds ratios and 95% confidence intervals across studies. - Results - We found nine eligible studies enrolling 17,109 women. Pregnancy was associated with a significant risk increase in developing varicose veins. The results of our meta-analysis suggest that the odds for women with a history of pregnancy in developing varicose veins significantly increases by 82% (odds ratio, 1.82; 95% CI, 1.43-2.33) compared with women with no history of pregnancy. As expected for epidemiologic observational studies, the heterogeneity was considerably high (I2 = 81%). - Conclusions - Our meta-analysis strongly supports the hypothesis that there is a significant and strong association between a history of pregnancy and varicose veins. However, qualitative and quantitative differences among studies were evident and were also reflected in a considerably high heterogeneity.
Gesehen am 30.04.2020